Estágio obrigatório no curso de Pedagogia : um estudo exploratório a partir da percepção dos licenciandos - Sartor, Jussane (2013)
This research for the Master's program in Post-Graduation in Education, proposed to study the perceptions of students of Pedagogy of the Federal University of Mato Grosso (UFMT) - Cuiabá Campus - on the internship experience. The theoretical study was conducted with reference to the political philosophy of Hanna Arendt (1906-1975), the conception of curriculum and pedagogical practice of Sacristán (2000), and the work of Brazilian researchers in the field of education and teacher training such as Gatti (2011), Pimenta e Lima (2011) e Lüdke (2009). The research sought to analyse the perception of students on the experience of internship, to verify which aspects would be revealed about the professional practice, and which of aspects would stand out. Data collection was carried out through questionnaire, using open and closed questions with 53 students. Through the free word association technique, which allowed access to the most spontaneous material amongst the participants, five main categories were established: "Curricular Action" (AC) presented the impression of participants of the school environment; "Professional Competences" (CP) was about the attitude and conduct necessary to pursue the teaching profession; " Intersubjective Relations" (RI) pointed to the affective investments and fondness caused by relationships established during the internship; "Teaching Profession" (PE) raised the discussion of the teacher as a profession, and "Imputed Importance" (IA) indicated the appreciation of internships by students. The result of processing the replies presented descriptive statistics in terms of frequency (%F), Average Evocation Order (OME), and Average Importance Order (OMI) to the impact of rationalization in the formulation of evocations: AC= 32,8 (%F), 3,1 (OME), 2,7 (OMI); CP= 27,4 (%F), 3,1 (OME), 2,7 (OMI); RI= 21,2 (%F), 3,0 (OME), 3,2 (OMI); PE= 17 (%F), 2,6 (OME), 2,9 (OMI); IA= 1,7 (%F), 3,3 (OME), 3,5 (OMI). The overall analysis of the data allowed me to infer that for the group studied, internship was set as a time of learning, in which the teaching praxis was the driving element of learning. This allowed the planning of self professional development from the theoretical and practical observation, and the systematization of knowledge, as well as the possibility of the reorganization of the relation between the future professional with the internship itself through the realization of teaching.